Women farm fish: Gender and commercial fish cage culture on the upper Ping River, Northern Thailand - Phimphakan Lebel (2018)
Studies from around the world underline the work of women in household-based aquaculture. Many extension and rural development programs and some commercial activities target women. Over the past decade, a tilapia fish cage industry has emerged on the Upper Ping River in northern Thailand. We interviewed 38 fish farmers, both women and men, about their practices and decision-making behavior and exploring gender relations. In addition, we collected quantitative data from 275 fish farms that allowed comparison of farming practices of women and men, and in a second survey compared 200 households that have farmed fish with 200 that have not to explore gender issues in access and decision-making. Women are frequently engaged in a day-to-day management of fish farms, most often working as part of a household team, but sometimes in senior management positions. Women attend trainings, and their experience and skills are largely recognized by male counterparts. Fish farms managed by men, women, or jointly yield similar profits. Women who farm fish for commercial profit are often empowered by such engagement within households. But empowerment in one arena does not easily translate into decision-making authority in others; few women hold real authority in community affairs and those who do so have primarily risen to prominence within women's groups or with respect to women's issues. Successful engagement in aquaculture, arguably, contributed to such success, but also benefited from a social position relative to both women and men.